Pengembangan Model Penilaian Sekolah Efektif - Subandi Subandi (Islamic University of Indonesia, 2008)
A general purpose of the programe is for developing model of effectiveschool assessment with its instrument and guidance of its applicationin order to do self-evaluation and self improvement, and effectivenessimprovement of school organization functions toward being able to productout puts quality which hoped. A specific purpose of the programe is fordeveloping; (1) construction and indicators of effective school, (2) severalinstruments for assessing effective school, (3) system of effective schoolassessment and its application guidance, and (4) recommendation ofimplementation for assessing effective school. This development is relatedmore deeply with improving educational quality in school. Therefore,educational quality in school is a function of quality in put showingstudent’s potentialities, quality of learning experience showing teacher’sprofessional ability, quality of using learning facilities, and quality ofheadmaster leadership showing school culture.